2019
DOI: 10.30862/jipvet.v8i2.18
|View full text |Cite
|
Sign up to set email alerts
|

Potensi Isi Rumen Sapi Asal Rumah Potong Hewan Sebagai Pakan Ternak Ruminansia Di Kabuaten Manokwari

Abstract: The aim of this resarch is to determine the potential of   rumen  content of cattle from slaughterhouse as ruminants   feed in Manokwari District, judging   from quantity (fresh and dry weight), Quality (DM and OM content), and physical characteristics.  Data of research analyzed by tabulation and T-Test. The results showed that each cow that is cut produces an average rumen content  of 8.507, 88 g  fresh weight or 1.127,16 g  dry weight with DM content 89,14%   and  OM content 89,83%. The average daily cattle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Further research carried out by Lestari et al (2017) stated that cow rumen content compost applied to pea plants showed an effect on the growth and production of pea plants by experiment using Completely Randomized Design (CRD). Further research conducted by Kocu et al (2018) to know the potential content of the rumen contents of cows seen from the quantity (fresh weight and dry weight) of the contents of the rumen contents of cows, the quality (dry matter and organic matter) of the contents of the cow's rumen and the physical characteristics of the contents of the cow's rumen. By using the descriptive method with the case study technique.…”
Section: Introductionmentioning
confidence: 99%
“…Further research carried out by Lestari et al (2017) stated that cow rumen content compost applied to pea plants showed an effect on the growth and production of pea plants by experiment using Completely Randomized Design (CRD). Further research conducted by Kocu et al (2018) to know the potential content of the rumen contents of cows seen from the quantity (fresh weight and dry weight) of the contents of the rumen contents of cows, the quality (dry matter and organic matter) of the contents of the cow's rumen and the physical characteristics of the contents of the cow's rumen. By using the descriptive method with the case study technique.…”
Section: Introductionmentioning
confidence: 99%